Generation and initial characterization of novel tumour organoid models to study human pancreatic cancer‐induced cachexia. Issue 6 (13th October 2020) - Vaes, Rianne D.W.; van Dijk, David P.J.; Welbers, Tessa T.J.; Blok, Marinus J.; Aberle, Merel R.; Heij, Lara; Boj, Sylvia F.; Olde Damink, Steven W.M.; Rensen, Sander S.
Abstract: Background: The majority of patients with pancreatic cancer develops cachexia. The mechanisms underlying cancer cachexia development and progression remain elusive, although tumour‐derived factors are considered to play a major role. Pancreatic tumour organoids are in vitro three‐dimensional organ‐like structures that retain many pathophysiological characteristics of the in vivo tumour. We aimed to establish a pancreatic tumour organoid biobank from well‐phenotyped cachectic and non‐cachectic patients to enable identification of tumour‐derived factors driving cancer cachexia. Methods: Organoids were generated from tumour tissue of eight pancreatic cancer patients. A comprehensive pre‐operative patient assessment of cachexia‐related parameters including nutritional status, physical performance, body composition, and inflammation was performed. Tumour‐related and cachexia‐related characteristics of the organoids were analysed using histological stainings, targeted sequencing, and real‐time–quantitative PCR. Cachexia‐related factors present in the circulation of the patients and in the tumour organoid secretome were analysed by enzyme‐linked immunosorbent assay. Results: The established human pancreatic tumour organoids presented typical features of malignancy corresponding to the primary tumour (i.e. nuclear enlargement, multiple nucleoli, mitosis, apoptosis, and mutated KRAS and/or TP53 ). These tumour organoids also expressed variable levels of many known cachexia‐related genes including interleukin‐6 ( IL‐6 ), TNF‐α, IL‐8, IL‐1α, IL‐1β, Mcp‐1, GDF15, and LIF . mRNA expression of IL‐1α and IL‐1β was significantly reduced in organoids from cachectic vs. non‐cachectic patients ( IL‐1α : −3.8‐fold, P = 0.009, and IL‐1β : −4.7‐fold, P = 0.004). LIF, IL‐8, and GDF15 mRNA expression levels were significantly higher in organoids from cachectic vs. non‐cachectic patients ( LIF : 1.6‐fold, P = 0.003; IL‐8 : 1.4‐fold, P = 0.01; GDF15 : 2.3‐fold, P < 0.001). In line with the GDF15 and IL‐8 mRNA expression levels, tumour organoids from cachectic patients secreted more GDF15 and IL‐8 compared with organoids from non‐cachectic patients (5.4 vs. 1.5 ng/mL, P = 0.01, and 7.4 vs. 1.3 ng/mL, P = 0.07, respectively). Conclusions: This novel human pancreatic tumour organoid biobank provides a valuable tool to increase our understanding of the mechanisms driving cancer cachexia. Our preliminary characterization of the secretome of these organoids supports their application in functional studies including conditioned medium approaches and in vivo transplantation models.